Work in prisons in Peru and its adaptation to international human rights standards - Rodríguez Salazar, Aníbal Ruivo (2023)
The author analyses the main international instruments related to the right to work, the purposes of punishment and the penitentiary regime, and the way in which they delimit the work carried out inside prisons by inmates, as well as identifying the international standards in force for their approach. Subsequently, it reviews the provisions of the Political Constitution of Peru applicable to prison work, as well as the Penal Enforcement Code and the new Legislative Decree No. 1343, which creates the Productive Prisons Programme, the main rules that regulate such work, in order to determine whether they are in line with the aforementioned standards of human rights protection and examine the problems generated by the lack of recognition of the labour link of work carried out inside prisons.